A TfR-Binding Cystine-Dense Peptide Promotes Blood–Brain Barrier Penetration of Bioactive Molecules. Issue 14 (26th June 2020) - Crook, Zachary R.; Girard, Emily; Sevilla, Gregory P.; Merrill, Morgan; Friend, Della; Rupert, Peter B.; Pakiam, Fiona; Nguyen, Elizabeth; Yin, Chunfeng; Ruff, Raymond O.; Hopping, Gene; Strand, Andrew D.; et al.
Abstract: The impenetrability of the blood–brain barrier (BBB) to most conventional drugs impedes the treatment of central nervous system (CNS) disorders. Interventions for diseases like brain cancer, neurodegeneration, or age-associated inflammatory processes require varied approaches to CNS drug delivery. Cystine-dense peptides (CDPs) have drawn recent interest as drugs or drug-delivery vehicles. Found throughout the phylogenetic tree, often in drug-like roles, their size, stability, and protein interaction capabilities make CDPs an attractive mid-size biologic scaffold to complement conventional antibody-based drugs. Here, we describe the identification, maturation, characterization, and utilization of a CDP that binds to the transferrin receptor (TfR), a native receptor and BBB transporter for the iron chaperone transferrin. We developed variants with varying binding affinities ( K D as low as 216 pM), co-crystallized it with the receptor, and confirmed murine cross-reactivity. It accumulates in the mouse CNS at ~ 25% of blood levels (CNS blood content is only ~ 1%–6%) and delivers neurotensin, an otherwise non-BBB-penetrant neuropeptide, at levels capable of modulating CREB signaling in the mouse brain. Our work highlights the utility of CDPs as a diverse, easy-to-screen scaffold family worthy of inclusion in modern drug discovery strategies, demonstrated by the discovery of a candidate CNS drug delivery vehicle ready for further optimization and preclinical development. Graphical abstract: Unlabelled Image Highlights: Blood–brain barrier penetration is key to treating central nervous system diseases. A drug-like cystine-dense peptide that binds transferrin receptor was identified. Brain accumulation and pharmacodynamic effect of peptide cargo were seen. This peptide represents a small (5 kDa) tag permitting CNS delivery of therapeutics.